An Analysis of Key Factors Influencing Job Burnout Among University Teachers in Tangshan - Wang, Xiaomin (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study investigates the influence of five independent variables—Job Characteristics, Work-Family Conflict, Perceived Organizational Support, Quality of Working Life, and Psychological Well-being—on a dependent variable, Job Burnout. Additionally, it aims to identify significant differences among these variables. Research design, data and methodology: This study employed the Index of Item-Objective Congruence for validity testing and Cronbach’s Alpha (n = 30) in a pilot test to assess reliability. Data collection involved 80 valid questionnaires from students at Yunnan Vocational College of Agriculture, which were analyzed using multiple linear regression to examine significant relationships between variables. Following this, a 12-week strategic plan (SP) was implemented for 40 students. To evaluate its effectiveness, quantitative results from current-SP and expected-SP were compared and analyzed using a paired sample t-test. Results: The analysis revealed that Job Characteristics, Work-Family Conflict, and Psychological Well-being had a significant impact on Job Burnout, whereas Perceived Organizational Support and Quality of Working Life did not. Finally, the results of the paired-sample t-test demonstrated significant differences in Job Burnout between Current-SP and Expected-SP. Conclusions: This research aims to analyze the factors influencing teachers’ job burnout in the context of Tangshan, China. Job Characteristics, Work-Family Conflict, and Psychological Well-being are key factors that policymakers and universities should address to create a more sustainable and supportive work environment.